EFEKTIVITAS PENAMBAHAN SUKROSA TERHADAP KARAKTERISTIK YOGHURT MANGGA (Mangifera indica L.) SEBAGAI RANCANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI SMA - ', Jumari; Sayuti, Irda; ', Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research to determine to learn the function of lactat acid bacteria (LAB) in food. This research did among march until may 2016. Result from this research to make desaign course such as student worksheet in biology SMA. This research did by 2 phases, field research and desaign course learning. Experiment mode used in this research. Making yoghurt mango started by pasteuritation procces,colding,innoculate,and incubation. Result of this research are lactad acid,pH, viscocity,and fat level. Result from this research used for desaign learning course as student worksheet in conventional biotecnology in SMA .Keywords : yoghurt, lactic acid bacteria , sucrose , design , student worksheet